2013
DOI: 10.1002/cne.23352
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the olivocerebellar projection of the chick: An axonal reconstruction study

Abstract: The projection pattern of the olivocerebellar (OC) axons, which terminate mainly as climbing fibers (CFs) in the cerebellar cortex, tightly reflects the compartmental and developmental organization of the cerebellum as revealed by mapping and reconstruction studies in the rat. The avian cerebellum is well lobulated and longitudinally compartmentalized like the mammalian cerebellum. However, the projection pattern of the OC axons has not been studied in detail for most areas of the avian cerebellum. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 53 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…Projections were classified according to the position of the origin within the DL and the position of the labeled climbing fibers in the cerebellar cortex, which were topographically related to each other (A-E). Two additional cases of similar anterograde labeling (F), in which aldolase C was not immunostained are cited from our previous study (Sasamura et al, 2013) and shown for comparison to others. For anterograde labeling experiments, the injection site is shown with a colored spot circumscribed by a continuous black line in the inferior olive and the labeled climbing fibers are shown with dots in the same color in the cerebellar cortex.…”
Section: Summary Of Anterograde and Retrograde Labeling Experimentsmentioning
confidence: 75%
See 4 more Smart Citations
“…Projections were classified according to the position of the origin within the DL and the position of the labeled climbing fibers in the cerebellar cortex, which were topographically related to each other (A-E). Two additional cases of similar anterograde labeling (F), in which aldolase C was not immunostained are cited from our previous study (Sasamura et al, 2013) and shown for comparison to others. For anterograde labeling experiments, the injection site is shown with a colored spot circumscribed by a continuous black line in the inferior olive and the labeled climbing fibers are shown with dots in the same color in the cerebellar cortex.…”
Section: Summary Of Anterograde and Retrograde Labeling Experimentsmentioning
confidence: 75%
“…This was presumably partly because the olivocerebellar projections have transverse branching in lobules IXc and X (green dots in Fig. C; Pakan et al, ; Sasamura et al, ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations